A history of African popular culture - Barber, Karin 1949- (Cambridge, [England] Cambridge University Press, 2018)
Popular culture in Africa is the product of everyday life: the unofficial, the non-canonical. And it is the dynamism of this culture that makes Africa what it is. In this book, Karin Barber offers a journey through the history of music, theatre, fiction, song, dance, poetry, and film from the seventeenth century to the present day. From satires created by those living in West African coastal towns in the era of the slave trade, to the poetry and fiction of townships and mine compounds in South Africa, and from today's East African streets where Swahili hip hop artists gather to the juggernaut of the Nollywood film industry, this book weaves together a wealth of sites and scenes of cultural production. In doing so, it provides an ideal text for students and researchers seeking to learn more about the diversity, specificity and vibrancy of popular cultural forms in African history.
Popular culture before 1900 -- Mines, migrant labour and township culture -- The city and the road -- The crowd, the state -- and songs -- The media -- globalisation and deregulation from the 1990s till today -- Conceptualising change in African popular culture.
Includes bibliographical references and index.
Keywords: Popular culture -- Africa, Sub-Saharan -- History; Africa, Sub-Saharan -- Social life and customs